1865-66 N.C. Sess. Laws 63 - (:unkn) unknown (My University, 1866)
Priv. Laws, ch. 7, § 19: Granted the Board of Aldermen the power to levy a fifty dollar tax on every pistol, Bowie-knife, dirk, sword-cane, or any other deadly weapon worn upon the person except a pocket knife without special permission from the aldermen.
Keywords: TAX - PROPERTY OR SALES